Curbing Delay of Justice on Ground of Jurisdiction in the Nigerian Courts: Lessons from the Islamic Law - Ishola, Abdullahi Saliu; Abikan, Abdulqadir I. (NIU Journal of Social Sciences, 2017)
Delay of trials is a big hiccup to the administration of justice in Nigeria. Delay is usually caused by litigantâ€™s challenge to the jurisdiction of the trial court and appealing the courtâ€™s ruling all through the hierarchy of the appellate system, taking decades, sometimes, to resolve. The Supreme Court has severally lamented over this abuse of court processes yet, no â€˜judicial or legislative willâ€™ has been employed to stop it. This research therefore analyses the manners by which justice is delayed and/or denied by challenging the courtâ€™s jurisdiction and exercising right of appeal. It finds that the lamentation by the apex court on the abuse of the process cannot solve the problem. It presents the Islamic law approach to the issue as a more balanced alternative and recommends its adoption along with constitutional amendment. It propounds the theory of Finality in Favour of Jurisdiction â€œFiFoJâ€ for adoption in the alternative. Keywords: Justice, Delay, Nigeria, Islamic Law.